ANALISIS PEMBAGIAN DEVIDEN PADA PERUSAHAAN YANG TERCATAT DI BEI - Hermanto Hermanto (Jurnal Akuntansi Bisnis, 2018)
The purpose of this study was to examine the role and return of investment securities in the form of dividends to maximize investor expectations. This study has a causality design with hypothesis testing. Data sources are secondary from the financial statements of issuers that distribute dividends during the years 2008-2012. Sampling using purposive sampling technique. The unit of analysisis the firm. The method of analysis is using multiple regression. The results showed that simultaneous ROE, PER, and WCTT influence DPR. Partially PER positively affects ROE, while WCTT and ROE has no effect to DPR. The study's findings showed PER dominant influence DPR, so that accounting information has value of relevance of accounting with investment decisions. The result shows that the accounting information has a function as a signal.Keyword : DPR, ROE, PER, WCTT, Debt